Planning of the house - Paulsen, Nell (My University, 1905)
Introduction: There are four things which must be considered in building a house, namely, special needs of the family, funds available for expenditures, location, and soil. The soil is divided into two classes, pervious and impervious; the former permitting the water so percolate freely through it while the latter being of very compact nature, prevents sub-surface drainage. Gravel, sand, and soft limestone are instances of the first class, clays being of an impervious nature. The nature of the soil must be given greatest consideration in deciding upon a location for health depends largely upon the condition of the soil. Low poorly drained grounded in productive of a great many of the most dreaded diseases while highly porous soil is freest from germs of diseases. The dry porous soil is essential to the maintenance of good health. Many soils contain decomposing organic matter, the gases from which if allowed to enter the house are very injurious to the health.
Citation: Paulsen, Nell. Planning of the house. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Home Sanitation; Special Needs of the Family; Preventing Dampness; Theses; Manuscripts (documents)